Luffa Cylindrica as a natural adsorbent of cyanide ion in aqueous médium (2017)
Cyanide is considered a highly toxic species for any ecosystem in as much as it causes disease in humans, contributes to the loss of soil fertility and contaminates water sources, constituting an important factor in the mortality of aquatic flora and fauna. The aim of this work is to evaluate the potential ability of the natural sponge Luffa Cylindrica as an adsorbent material to remove cyanide from aqueous medium. In order to measure the adsorption capacity the experiments were carried out through the application of a factorial experimental design that includes variables such as pH and contact time. Suitable conditions to retain the cyanide ion were pH 9.0 and a contact time of 10 minutes. The adsorption behavior is represented by the Freundlich isotherm, and the adsorption kinetics fits the pseudo-second order kinetic model. Retention rates from 12.2 to 98.0%.